Prevalence of Toxoplasma gondii Antibodies in Individuals Occupationally Exposed to Livestock in Portugal - Almeida, D (2022)
Toxoplasmosis is a worldwide zoonotic disease with different and complex routes for transmission. Workers occupationally exposed to animals or raw meat and viscera (WOE) may be at more risk than the general population, however conflicting data exist on the risk of developing toxoplasmosis due to this close contact. To add knowledge to this topic, the aim of the present study was to ascertain if WOE were more likely to be anti-T. gondii IgG seropositive than the general population as well as to study risk factors for T. gondii infection such as professional activity, gender, age, years of work and region. For this purpose, a case–control study using archived samples was setup. A total of 114 WOE (including pig slaughterhouse workers, butchers, veterinarians and farmers) and 228 anonymous volunteers (matched with cases by region, age and gender) were studied for anti-T. gondii IgG. A significantly higher anti-T. gondii IgG occurrence (p = 0.0282) was found in WOE when compared with the general population (72.8% [CI = 64.6–81.0%] versus 60.1% [CI = 54.6–65.6%]). Multivariate analysis showed that WOE of more than 50 years of age were more likely to be seropositive for anti-T. gondii IgG (aOR = 16.8; 95% CI 3.6–77.5; p < 0.001) than those aged less than 50 years. To our knowledge, this is the first case–control study on the prevalence of anti-T. gondii IgG in WOE in Portugal, also showing an added risk for T. gondii infection in those exposed to animals or their meat and viscera. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.